A new simple test against spurious long memory using temporal aggregation - Heri Kuswanto (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2009)
We have developed a new test against spurious long memory based on the invariance of long memory parameter to aggregation. By using the local Whittle estimator, the statistic takes the supremum among combinations of paired aggregated series. Simulations show that the test performs good in finite sample sizes, and is able to distinguish long memory from spurious processes with excellent power. Moreover, the empirical application gives further evidence that the observed long memory in German stock returns is spurious.
Keywords: C12; C22; 330; Local-Whittle method; Spurious long memory; Change point; Aggregation; Zeitreihenanalyse; Statistischer Test; Theorie